Recent progress in the total synthesis of pyrrole-containing natural products (2011–2020). Issue 19 (2nd July 2021) - Singh, Nidhi; Singh, Snigdha; Kohli, Sahil; Singh, Aarushi; Asiki, Hannah; Rathee, Garima; Chandra, Ramesh; Anderson, Edward A.
Abstract : This review discusses total syntheses of pyrrole-containing natural products over the last ten years, highlighting recent advances in the chemistry of pyrroles in the context of their innate reactivity, and their preparation in complex settings. Abstract : Natural products have long served as a rich resource for drug discovery in the treatment of illnesses and chronic diseases. Among many families exhibiting fascinating structural complexity and impressive bioactivity, pyrrole-containing natural products frequently present a significant challenge to practitioners of organic synthesis. As a result, synthetic chemists have paid intense attention to the construction of such frameworks, not least as the amounts of natural product isolated from their natural source is often far less than that needed for biological testing. This review discusses total syntheses of pyrrole-containing natural products over the last ten years, highlighting recent advances in the chemistry of pyrroles both in the context of their innate reactivity, and their preparation in complex settings.